Sterilization Analysis In The Bakauheni Ferry Port Of Lampung Province - Bambang Setiawan; Dahlia Dewi Apriani; Wahyu Hadinata (IWTJ : International Water Transport Journal, 2021)
The Bakauheni Ferry Port is managed by PT. ASDP Indonesia Ferry as port operator , province BPTD Wilayah VI Provinsce Bengkulu and Lampung as a government representative in the port. Crossing the harbor Ba kauheni Located in South Lampung regency province of Lampung . Bakauheni Ferry Port is one of the largest ferry ports in Indonesia with a total of 71 ships and has 7 dock units which are divided into 1 (one) executive dock and 6 (six) regular docks, in the implementation of its operations there are several obstacles that are quite important to overcome such as the problem of implementing sterilization at the Executive Terminal which is not good enough, causing many service users to have activities in the Port area such as trading in the parking area ready to load vehicles, this can occur due to a lack of signs and support for sterilization at the Port, besides that there is still crossing between vehicles in area B3 which is an area ready to load vehicles onto ships. To analyze this, the author refers to PM Number 29 of 2016 concerning the sterilization of ferry ports, PM Number 13 of 2014 Traffic Signs and Decree of the Director General of Land Transportation Number SK, 242 / HK.104 / DRJD / 2010 regarding Technical Guidelines for Traffic Management cross crossing. The analysis used is the analysis of sterilization at the Executive Terminal, Analysis of Needs for Signs at the Executive Terminal and Analysis of Traffic Management at the Executive Terminal. In order to overcome the existing problems, it will be adjusted to the Regulation of the Minister of Transportation Number 29 of 2016 concerning the Sterilization of Ferry Ports such as implementing zone arrangements in accordance with the Regulation of the Minister of Transportation Number 29 of 2016 concerning Sterilization of Ferry Ports so that service users will know which zones they are allowed to use. carry out activities and add equipment that supports sterilization such as land signs, road markings to make it easier for service users to reach their destination at the Executive Terminal, besides that, traffic management arrangements for delivery / pick-up vehicles will also be implemented so as not to enter prohibited areas so as to avoid crossing between vehicles in accordance with the Regulation of the Director General of Land Transportation Number: SK.242 / HK.104 / DRJD / 2010 concerning Technical Guidelines for Traffic Management at Crossings.